Correction: Nazeer et al. Bacterial-Specific Aggregation and Killing of Immunomodulatory Host Defense Peptides. Pharmaceuticals 2021, 14, 839 - Nauman Nazeer; Juan Carlos Rodriguez-Lecompte; Marya Ahmed (MDPI AG, 2024)
In the original publication [...]